The Influence of Principal's Leadership on Teacher Performance - Dian Dian; Roni Suhendar; Sovian Sovian (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aims to find out how the principal is in his leadership and how influential the principal's leadership is on teacher performance. The method used in this research is descriptive using a quantitative approach. Data collection was obtained from questionnaires, interviews, and documentation studies. While the data analysis uses percentage techniques for descriptive data and test eta quadrat for quantitative data. The results obtained in this study explain that the principal's leadership is in the very good category with a percentage gain of 94.6%.Teacher performance is in the very good category with a percentage gain 80.5%. The results of linear regression calculations show that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. Principal leadership contributes 37.6% to teacher performance. Which means principals have an important role in teacher performance.